E-Governance in Local Authority – A Pilot Study with Reference to Tirupur City, Tamil Nadu - Karpagavalli, V.; Mohanasoundari, R. (Indian Journal of Computer Science, 2017)
Information and Communication Technology (ICT) is rapidly gaining the center stage for future world economic growth and development. The advances in information and communication technologies and their related infrastructure apparatus provide opportunities to transform the relationship between government and citizens and business in new ways that contribute to the attainment of good governance. The advancement in ICT not only acts as an engine for economic growth, it also enhances the potential for the delivery of social services and the effectiveness of government administration. In addition, the use of ICT may lower transaction costs both for citizens and government operations and make public services more affordable to people at large. India being the largest democracy in the world, has much to gain from e-Governance, especially when citizen participation in governance is one of the features of the fully evolved stage of e-government. Government of India has for the past three decades (1985-2015) widely acknowledged that expanded use of ICT in the public sector can offer important benefits such as improved planning and monitoring mechanisms, cost savings through rationalization, and more effective administration and delivery of certain public services. E-governance needs to transform all levels of government but the focus should be on local governments since local governments are the closest to citizens, and constitute for many, the main interface with upper tiers of government. The relationship of citizens and local authorities tends to be one based on proximity as the interests at stake for both parties are closely intertwined concerning issues such as public services, local development, education etc. Thus, e-governance based administrative reforms in local governments can have maximum impact on citizens as well as employees working in Panchayati Raj.